Sources of knowledge flow between developed and developing nations - Laurie Ciaramella; Gaétan de Rassenfosse; Florian Seliger (ETH Zurich, KOF Swiss Economic Institute, 2018)
This paper provides a long-term view on the sources of knowledge flow between developed and developing nations. It relies on patent data to explore three potential sources: R&D collaboration, technology sourcing, and technology transfer. All three sources provide a very consistent message. First, knowledge flows with East Asia, particularly China, are occurring more frequently. Second, knowledge flows are increasingly concentred in information and communication technologies. Third, the United States & Canada had traditionally larger patenting activity with Asia than Europe, but the share of activity between Europe and Asia has been increasing in recent years. Fourth, larger patenting activity between the United States & Canada and Asia implies that the U.S./Canada region is more likely to benefit from reverse knowledge flows as China progresses towards becoming a technological leader.
Keywords: 330; international technology sourcing; R&D offshoring; R&D collaboration; technology transfer; patent